2016
DOI: 10.1007/s11664-016-4890-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Energy Conversion Efficiency of Thermoelectric Materials: Constant Property Versus Average Property Models

Abstract: Maximum thermoelectric energy conversion efficiencies are calculated using the conventional ''constant property'' model and the recently proposed ''cumulative/average property'' model (Kim et al. in Proc Natl Acad Sci USA 112:8205, 2015) for 18 high-performance thermoelectric materials. We find that the constant property model generally predicts higher energy conversion efficiency for nearly all materials and temperature differences studied. Although significant deviations are observed in some cases, on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Alternatively a cumulative property model can be used to conclude on, which was proposed by Kim et al [21] and which accounts for the temperature dependency of material properties by means of a different expression for the maximum efficiency with the use of a so called engineering figure of merit. A recent analysis for 18 high-performance thermoelectric materials by Armstrong et al [22] revealed an overestimated prediction of  by the constant property model compared to the cumulative model, which equalled a factor of 1.16 on the average. Regardless of the chosen model for TEM efficiency a pure analytic or simulation-based determination of TEM properties on the base of experimentally determined material properties is subjected to significant errors too, due to necessitated assumptions on elusive electric and thermal coupling conditions and inherent uncertainties of the applied characterization methods.…”
Section: Module Characterization Techniquesmentioning
confidence: 99%
“…Alternatively a cumulative property model can be used to conclude on, which was proposed by Kim et al [21] and which accounts for the temperature dependency of material properties by means of a different expression for the maximum efficiency with the use of a so called engineering figure of merit. A recent analysis for 18 high-performance thermoelectric materials by Armstrong et al [22] revealed an overestimated prediction of  by the constant property model compared to the cumulative model, which equalled a factor of 1.16 on the average. Regardless of the chosen model for TEM efficiency a pure analytic or simulation-based determination of TEM properties on the base of experimentally determined material properties is subjected to significant errors too, due to necessitated assumptions on elusive electric and thermal coupling conditions and inherent uncertainties of the applied characterization methods.…”
Section: Module Characterization Techniquesmentioning
confidence: 99%
“…where , TH, and TC are the Carnot efficiency ( − ), hot junction temperature, and cold junction temperature values, respectively. (Armstrong et al, 2017). The quantity Z is a dimensionless TE figure of merit used to evaluate the performance of a TE material, where ZTavg is the Z value (often written as ZT) at the average temperature of a projected operating range (Armstrong et al, 2017).…”
Section: Engineering Fundamentals Of the Problemmentioning
confidence: 99%
“…(Armstrong et al, 2017). The quantity Z is a dimensionless TE figure of merit used to evaluate the performance of a TE material, where ZTavg is the Z value (often written as ZT) at the average temperature of a projected operating range (Armstrong et al, 2017). The TE figure of merit can be described by:…”
Section: Engineering Fundamentals Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies of magnetoelectric coupling involve such heterostructures as Fe/BaTiO 3 [19], Co 2 MnSi/BaTiO 3 [20], [21], Fe(Ni,Co,CrO 2 )/BaTiO 3 /normal metal [22] etc. Recent paper considered a supercell of ferromagnetic perovskite Sr-doped LaMnO 3 and ferroelectric BaTiO 3 [23]. The spontaneous electrical polarization of BaTiO 3 causes the accumulation of spin-polarized electrons in the ferromagnetic half-metallic La 1−x A x MnO 3 layer at the interface perpendicular to the direction of polarization.…”
Section: Introductionmentioning
confidence: 99%